Estimasi Proporsi Mahasiswa dengan Tingkat Stres Tinggi - Evan Hardyansah; Fandy Azkan Nufus; Ferdy Adhi Wijaya; Gulfia Aufa Rafiki; Perani Rosyani (CV. Multi Kreasi Media, 2026)
Stress is a psychological response that arises when individuals face demands exceeding their adaptive capacity. University students are considered a vulnerable group to stress due to academic demands, social pressure, and adjustment to the higher education environment. This study aims to estimate the proportion of students experiencing high stress levels using an inferential statistical approach. This research employed a quantitative method with a survey design. Data were collected through a stress-level questionnaire distributed to student respondents. The questionnaire results were classified into stress categories, namely low, moderate, and high. Data analysis was conducted by estimating the proportion of students with high stress levels and determining the confidence interval to describe the accuracy of the population estimation. The results indicate that a certain proportion of students experience high stress levels within the specified confidence interval. These findings suggest that academic stress among students is a significant issue that requires attention. The results of this study are expected to serve as a reference for higher education institutions in developing stress prevention and management programs to support students’ mental health.